Flow of Thin Liquid Film on an Inclined Solid Surface - Khidr Khidr (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, we consider flow of thin liquid film on an inclined solid surface with an inclination angle . We use the Navier-Stokes equations to obtain equations that govern such flow .We solve these equations analytically with an appropriate boundary conditions to determine the thickness of the film for different values of the inclined angle .